2019
DOI: 10.3390/molecules24244447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Addition Time on the Nutritional Profile of Thunnus obesus Head Soup and the Formation of Micro/Nano-Sized Particle Structure

Abstract: In order to investigate the effects of salt on the nutrients and tastes profiles of big eye tuna head soup, the typical nutrients and taste substances were analyzed. The formation and the morphology of micro/nanoparticles (MNPs) were studied using an inverted optical microscope, and the interactions among components in MNPs were studied using a laser scanning confocal microscope. The results showed that the nutrients were dissolved to the maximum in the soup when salt was added at 150 min of cooking. Comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In the oil‐in‐water (O/W) emulsion system, most of the hydrolysed proteins are distributed in the water phase environment and cannot effectively act on the interface phase and the oil phase environment, where the oxidation reaction is the most concentrated (Zhang, 2014). The amino acids and sugar might undergo the Maillard reaction to produce flavouring substance during the boiling process (Qian et al , 2019; Fan et al , 2019). It is reported that antioxidant peptides with certain amino acids will strongly affected by the temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In the oil‐in‐water (O/W) emulsion system, most of the hydrolysed proteins are distributed in the water phase environment and cannot effectively act on the interface phase and the oil phase environment, where the oxidation reaction is the most concentrated (Zhang, 2014). The amino acids and sugar might undergo the Maillard reaction to produce flavouring substance during the boiling process (Qian et al , 2019; Fan et al , 2019). It is reported that antioxidant peptides with certain amino acids will strongly affected by the temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In the early stage, the microstructure of micro/nanocolloidal particles in big eye tuna head soup was investigated using laser scanning confocal microscopy and inverted optical microscope. It was found that the center of the colloidal particles is mainly TG, and the outer membrane is mainly phospholipids, and few protein particles are embedded (Fan et al., 2019; Qian et al., 2019). Meanwhile, EPA and DHA of big eye tuna head soup were found mainly existed in triglyceride and phospholipid molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Migration of nutritional components (e.g., lipid, protein, sugar, and other components) in tuna head soup and the effect of processing methods on them are necessary to be illustrated, which will be helpful to understanding the nutritional mechanism of tuna head soup for human beings. Our previous works found that micro/nanosized colloidal particles were formed in Atlantic salmon, bighead carp, and tuna head soups (12)(13)(14). After a series of chemical and physical reactions in the boiling process of tuna head soup, the chemical components included not only the original components migrated from the tuna head but also some newly formed components.…”
Section: Introductionmentioning
confidence: 98%